Normal-pressure hydrocephalus: A rare cause of reversible dementia. Issue 2 (February 2022) - Liang, Kyle; Chebrolu, Puja
ABSTRACT: Normal-pressure hydrocephalus (NPH) is characterized by the clinical triad of dementia, gait instability, and urinary incontinence. The estimated annual incidence is 1.8 cases in 100, 000 persons, making NPH a rare diagnosis and uncommon cause of dementia. NPH is a form of communicating hydrocephalus that can easily be missed in older adults with multiple comorbidities, so clinicians must exclude reversible causes of dementia before diagnosing irreversible causes such as Alzheimer disease.